Tinjauan Yuridis Pelaksanaan Eksekusi Lelang pada Perjanjian Kredit Macet dengan Hak Tanggungan - Jannah, Masitoh Miftahul; Badriyah, Siti Malikhatun (Fakultas Syariah INSURI Ponorogo, 2023)
Mortgage rights are born because of the underlying agreement, namely a credit agreement. The existence of a credit agreement results in the debtor being obliged to carry out his performance in the form of debt repayment to the creditor. If the debtor defaults, a legal action is taken in the form of execution, which is generally carried out by auction on Mortgage Rights. This type of research is normative which is descriptive. The data sources used are primary data and secondary data. With literature study data collection techniques. And using qualitative data analysis methods. With the existence of executorial power in the credit agreement, the creditor as the holder of the Mortgage Rights can take action to execute the auction of the land rights charged with the Mortgage Rights. Auction with Mortgage Rights is a class of execution auction, because it is based on a credit agreement. The implementation of the execution auction of Mortgage Rights must be carried out in accordance with the procedures of existing laws and regulations, so that there is a legal certainty, both for debtors, creditors, and auction winners.